A CHANGE-DETECTION APPLICATION ON THE EVOLUTION OF KAHAK PLAYA (SOUTH KHORASAN PROVINCE, IRAN) - Rezaei Moghaddam M.H.; Saghafi M. (My University, 2006)
Kahak salt playa in South Khorasan province of Iran, have special geomorphological characteristics by the presence of ephemeral saline lakes, wetlands, salt crusts, surface accumulations of salt and zones of patterned ground. Salt crusts in the soil surface are unique in the region and have laminated horizons in the playa soil. Soil-surface salt accumulations are dominated by NaCl and gypsum. It has been found that distribution of chemical soluble is not uniform across the playa landscape, and this result influences on the variety form of patterned ground. In this study, the percent changes in some of the chemical elements such as NaCl, gypsum and also brine extent have been calculated in the playa. Indicating changes in Kahak salt playa is the main aim of this study by using remote sensing and GIS techniques. In this paper, techniques such as spectral un-mixing, maximum likelihood classification, band rationing, fuzzy classification and correlation relationships are discussed. This contribution presents modeling of temporal and spatial changes of salinity and playa developing using combined approaches that incorporate different data-fusion and data-integration techniques for two periods of date. Furthermore, percent changes in the surface-patterned ground of the playa have been calculated using texture and pattern analysis of the PCA1. Results have revealed that, in the playa developing, chemical materials such as sodium, NaCl, gypsum and also brine extent are positively correlated with each other and the most increased changes are related to gypsum and the most decreased changes are related to the NaCl. Also changes in the amount of agricultural area in the playa-lakes margin, show low effects in the desertification process. © 2006 Springer-Verlag.
Keywords: CHANGE DETECTION; CHEMICAL CHARACTERISTICS; FUZZY CLASSIFICATION; KAHAK (IRAN); PLAYA; REMOTE SENSING